Answer:4.5
Step-by-step explanation:
A 0 1 2 3
B 0 1.5 3 4.5
V=x³-7x+6, V=(x-2)(x+3)*h
(x-2)(x+3)*h=x³-7x+6
h{x²+x-6}=x³-7x+6
h=(x³-7x+6)/(x²+x-6)
Therefore h=x-1
-----------------------------
Check answer:
V=(x-2)(x+3)(x-1)
=(x-1)(x²+x-6)
=x(x²+x-6)-1(x²+x-6)
=x³+x²-6x-x²-x+6
=x³-6x-x+6
=x³-7x+6
A. 72÷9÷2 = 8÷2 = 4
b. (18 ÷ 6) ÷ 3 = 3 ÷ 3 = 1
c. 45 ÷ 5 ÷ 3 = 9 ÷ 3 = 3
d. 144 ÷ (12 ÷ 2) = 144 ÷6 = 24
P(x) to P(x+2), you need to graph the same but shift 2 units to the left.
New function :
Max = 4 ,coordinate points (-5, 0) and (5,0)
Yeeeeeeeeeer eeee ee e e we. we e e we e e eeeee e e e e e e e e e e e